Comparison of the effect of Davis instructional strategy and traditional instructional on the development of reading skills of dyslexic boys in grade 2 of elementary school from Roshtkhar - Khoshroo, Mohsen; Rezaei, Ali Mohammad; Talepasand, Siavash (Majallah-i ravānshināsī va ravānʹpizishkī-i shinākht = Shenakht journal of psychology and psychiatry, 2021)
Introduction: Reading is one of the most important skills in elementary school so that its disorder affects learning of other subjects. Aim: This study aimed to compare the effect of Davis educational strategy with traditional education in improving the reading of dyslexic male students in the second grade of elementary school. Method: The research type was quasi-experimental. The population of this study included all boys in grade 2 of elementary school from Rashtkhar city in the academic year 2015-2016 that 10 of them who were dignosed with dyslexia, were randomly selected based on a checklist of 27 items for dyslexia symptoms, report card and health assessment card of the first year of elementary school. Then these students were randomly divided in experimental group with davis method intervention and the other group with traditional instruction. After Davis instructional intervention, post-test was performed on both groups and obtained data from pre-test and post-test were analyzed using SPSS version 19 with Kolmogorov-Smirnov test and dependent t-test. Results: The results of dependent t-test and difference between scores of the two groups showed that improvement mean in Davis group (8.15) compared to the traditional group (2.67) was significantly different, which indicates the effect of Davis treatment intervention on improving students' reading (P<0.01). Conclusion: It can be concluded that Davis method has improved students reading skills by increasing the range of precision and attention, improving visual memory and comprehension.